The Analysis of Fraud in Perspective of Fraud Pentagon Theory: An Empirical Study in Indonesia - Mashitoh, Heriyanni; Daurrohmah, Eka Wirajuang; Inan, Dedi Iskandar; Firman, Antares (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to delve into the primary causes of fraud, focusing on the fraud pentagon theory that encompasses all types of fraud in both the public and private sectors particularly in Indonesia. Using a qualitative phenomenological descriptive method, this study seeks to gain deep insights into individual subjective experiences, especially from the perspective of forensic auditors. These auditors are not only experts in investigating fraud but are also skilled in analyzing financial data, evaluating internal controls, and formulating recommendations based on their investigations. This research employs a semi-structured interview approach and involves 11 forensic auditors with CFE or CFrA certifications from both AUI of BPK and the ACFE Indonesian chapter. Through this analysis, the study offers a unique contribution to the literature by highlighting region-specific cultural and social dynamics, such as the profound reliance on religious-based justifications or political affiliations, adding complexity to the understanding of fraud in Indonesia.